2005
DOI: 10.1603/0022-0493-98.5.1648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kaolin on Fitness and Behavior of <I>Choristoneura rosaceana</I> (Lepidoptera: Tortricidae) Larvae

Abstract: The mechanisms by which kaolin, a clay particle film formulation, affects the fitness and behavior of larvae of obliquebanded leafroller, Choristoneura rosaceana (Harris), were investigated. Feeding experiments tested kaolin as a physical barrier versus a physiological toxin for larvae that consumed kaolin applied either to apple (Malus spp.) leaves or mixed in artificial diet. Behavioral experiments tested the effects of kaolin applied to apple leaves on neonate dispersal and leaf rolling by third and fourth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A previous study on using kaolin against a fruit fly found that it can operate as a tactile deterrent, lowering the time female Rhagoletis pomonella (Welsh) spends on treated fruits ( Leskey et al, 2010 ). Another study discovered that the leafroller Choristoneura rosaceana (Harris) neonate larvae dispersed more quickly from plants treated with kaolin ( Sackett, Buddle & Vincent, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on using kaolin against a fruit fly found that it can operate as a tactile deterrent, lowering the time female Rhagoletis pomonella (Welsh) spends on treated fruits ( Leskey et al, 2010 ). Another study discovered that the leafroller Choristoneura rosaceana (Harris) neonate larvae dispersed more quickly from plants treated with kaolin ( Sackett, Buddle & Vincent, 2005 ).…”
Section: Discussionmentioning
confidence: 99%